A stacked array antenna able to make a very large gain and tilt the end‐fire beam at the ISM‐band. Issue 9 (11th May 2019) - Lee, Changhyeong; Park, Heejun; Lim, Yongseok; Kahng, Sungtek
Abstract: In this article, an antenna is designed to generate an end‐fire radiated beam of a very large gain for a Printed Circuit Board (PCB) structure and steer the beam at an Industrial Scientific Medical (ISM)‐band. A flush‐mounted slot‐coupled feed and two parasitic layers can increase the antenna gain substantially. This single element is made to be a 1‐by‐8 array to generate a very high gain to deliver wireless power more than single element to the far‐field zone and spot the receiver of interest without interference toward others on the azimuth plane. Furthermore, four layers of this array are stacked to tilt the beam up and down on the elevation plane for target selectivity of a higher degree and more wireless‐power transfer. The antenna system is implemented with the substrate of Rogers 4350B and operated at 2.4 GHz as the ISM‐band service, and the validity of the proposed design is verified by electromagnetic numerical simulation and physical realization. The simulation and measurement of the fabricated 1D array antenna show nearly 19 and 16 dBi, respectively as high gains. The stacked structure as a 2D array generate the titled beam moving from −35° to 35° with the antenna gain from 17 to 20 dBi for a varying angle.